Working with Clients Who Choose Medical Assistance in Dying (MAID): A New Landscape for Counsellors - Walker, Anna; Wong, Gina (Canadian Journal of Counselling and Psychotherapy, 2018)
The passing of Bill C-14 legalized medical assistance in dying (MAID) in Canada in June 2016. As of October 2017, more than 2,000 Canadians had successfully utilized MAID. Currently, it remains unclear how to best serve the psychological needs of these individuals. The extant literature is reviewed to offer awareness and understanding about who chooses MAID. The rationale for this decision, the impact on family members, and changes in attitudes and experiences of death and dying are provided. Counsellor recommendations are discussed along with future research directions. A call is made to examine existing theories of death and dying to expand and reflect this new experience of dying.